The harmonious development of children of preschool age in the use of health of innovative technologies - Яворська [Tatyana Yavorskaya] Тетяна Євгенівна (Slobozhanskyi Herald of Science and Sport, 2013)
The article considers the unconventional and Wellness approaches to the use of balls-fitbol to harmonious development of the child of preschool age in physical education. The author studied the state of physical and mental health of children of senior preschool age; the effectiveness of the impact of fitbol gymnastics on the level of development of physical qualities of senior preschool age children; used modern methods of research and analysis of the results of the experiment; proved the effectiveness of the impact of fitbol gymnastics on the harmonious development of a child of preschool age in the process of usage of health-improving innovative technologies; considered the possibility of the introduction of the health of innovative technologies in the teaching practice of pre-school educational establishments; the results of the research were tested in the educational process of pre-school education of Zhytomyr